2019
DOI: 10.26822/iejee.2019349247
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 3D Multi-User Virtual Environments on Collaborative Learning and Social Presence

Abstract: Three-dimensional Multi-User Virtual Environments (MUVEs) are being increasingly used in many areas, and they are becoming more and more integrated with learning and teaching. MUVEs can be used in learning and teaching to facilitate student learning and collaboration. This study identified the effects of MUVEs on collaborative learning and social presence and investigated whether these effects varied by gender. The participants were sophomore students attending a programming language course. They used a MUVE f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…Together with voice communication, multi-user virtual environments enable the group members to exchange ideas in an authentic environment and reinforce CL. As long as technical problems are avoided, effective CL can be achieved in these environments (Shonfeld & Resta., 2019;Tüzün et al, 2019). Therefore, it is recommended that adopters discover which factors promote satisfaction in different environments.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Together with voice communication, multi-user virtual environments enable the group members to exchange ideas in an authentic environment and reinforce CL. As long as technical problems are avoided, effective CL can be achieved in these environments (Shonfeld & Resta., 2019;Tüzün et al, 2019). Therefore, it is recommended that adopters discover which factors promote satisfaction in different environments.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Earlier studies ( Kuznetcova, Teeple, & Glassman, 2018;Mascitti, Fasciani, & Stefanelli, 2012 ) argued the capacity of MUVEs to adapt to learner needs and create challenging tasks in context; they concluded that learner engagement occurred with the creation of an avatar mirroring one's identity and self-perceptions, which also contributed to the democratic atmosphere. Other studies ( Dieterle & Clarke, 2009 ;Stacy & Liz, 2008 ;Tilak et al, 2020 ;Tüzün et al, 2019 ) During pre-exploration process, students were exposed to tutorials for virtual simulation, simulation space visiting, and self-reflection method. Exploration is critical to get involved in lived experience.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian Umamah dan Muassomah (2020) mengintegrasikan pembelajaran kolaboratif dengan teknologi Whatsapp Group hanya saja pelaksanaannya sama dengan pembelajaran kolaboratif pada penelitian-penelitian lainnya. Penelitian pembelajaran kolaboratif dengan teknologi dilakukan oleh Tüzün et al (2019) degan menggunakan Multi-User Virtual Environments (MUVE) tiga dimensi untuk menguji efektifitas lingkungan belajar. Berbeda dengan penelitian ini yang mengkaji inovasi pembelajaran kolaboratif menggunakan metodologi Eduinnova.…”
Section: Pendahuluanunclassified